MENINGKATKAN KOSAKATA SISWA AUTIS MELALUI MEDIA UNO BERBANTUAN AUGMENTED REALITY - Istiqomah istiqomah; Aini Mahabbati (JPK (Jurnal Pendidikan Khusus), 2019)
This research is a classroom action research which aimed to improve the ability to master the vocabulary of animal names using UNO media assisted by augmented reality. The subject was an autistic student who had problems mastering the vocabulary of animal names at SLB Autisma Dian Amanah Yogyakarta. The research design used the Kemmis and Mc Taggart models. Data collection techniques used tests and observation. Learning outcomes test and student activity observation sheets were used as instruments. Data analysis techniques used are qualitative and quantitative. The results of this study UNO assisted with augmented reality improved the process and learning outcomes of animal name vocabulary in autistic students. The improvement process was supported by steps expaining and demonstraring ANIMO cards. Observing, shuffling, opening, and matching the color of the card. throwing on the base of the drawing. Mentioning the name and place of life of the animal. Increased learning outcomes in pre-action scored 36.7. Post-action I scored 60 and Post-cycle action II increased to 86.7.